First identification of a Neanderthal bone spear point through an interdisciplinary analysis at Abric Romaní (NE Iberian Peninsula) - Paula Mateo-Lomba; Andreu Ollé; Juan Luis Fernández-Marchena; Palmira Saladié; Juan Marín; M. Gema Chacón; Josep Vallverdú; Isabel Cáceres (Scientific Reports, 2024)
Abstract Osseous industry has been observed at an increasing number of Neanderthal sites. Bone fragments were used for practical purposes, and a range of bone shaping techniques were employed. The variability of bone tools observed in different assemblages reflects considerable functional diversity. However, no bone spear points have been reported from these contexts. A comprehensive analysis of a bone spear point from the Middle Palaeolithic site of Abric Romaní (Barcelona, Spain) is presented. Through an interdisciplinary, multi-technique, and multi-scale approach combining technology, taphonomy, and functional analysis, compelling evidence for manufacture, use, and hafting was uncovered. The specimen exhibits clear signs of intentional knapping. The presence of microscopic linear impact marks, an impact fracture at the tip and potential internal stress fractures indicate its use as a spear. Furthermore, the observed wear pattern and a morphological adjustment of the trabecular tissue support the hafting hypothesis. Abric Romaní contributes to our understanding of Neanderthal hunting behaviour and the significance of composite bone tools in their technological repertoire 50,000 years ago. This discovery highlights the flexibility and adaptability of Neanderthal technology, providing evidence of bone technology that is sometimes obscured in the archaeological record and offering valuable insights into their hunting strategies during the Middle Palaeolithic.